Kajian Komunikasi Interpersonal Orang Tua-Anak Dalam Perspektif Psikologi Komunikasi - Kholis, Nur; Warto (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the role of Artificial Intelligence (AI) as a learning companion for children and its impact on parent–child interpersonal communication from a communication psychology perspective. Employing a qualitative approach, the study involved in-depth interviews with 25 parents who actively use AI-based learning applications, along with content analysis of five AI learning platforms. Data were collected between August and October 2024 in the Jabodetabek region through semi-structured interviews, participatory observation, and digital content analysis. The findings reveal that the integration of AI into children’s learning creates a triadic communication dynamic involving parents, children, and technology, with 92% of participants reporting that AI has become a routine component of daily learning activities. AI offers positive contributions by enhancing learning accessibility (84%), enabling personalized learning, and reducing emotional conflict between parents and children (72%). However, AI use may also reduce the intensity of direct verbal communication (68%) and increase the risk of technological dependency among children (28%). The study identifies four effective communication strategies—active co-engagement, complementary role specialization, scheduled tech-free quality time, and critical digital literacy education to support balanced AI use while maintaining emotional bonds within families